Evaluation of the Labor Impact of the National Program of Direct Support to the Poorest - JUNTOS in Peru - Arpasi-Lima, Wilson Smith; Ticona-Campos, Varanny Nelyda; Rodríguez-Limachi, Omar Moisés; Yapuchura-Saico, Cristóbal Rufino; Incacutipa-Limachi, Duverly Joao; Ticona-Carrizales, Lucio (Journal of Ecohumanism, 2024)
The objective of this research is to estimate the labor impact of the National Program of direct support to the poorest JUNTOS in Peru for the year 2021. The methodology used is the Propensity Score Matching (PSM) through the nearest neighbor method; the database of the National Household Survey ENAHO 2021 is used as a source of information. The results of the logit model indicate that poverty, unsatisfied basic needs and education do influence the probability of participation in the Juntos Social Program and are statistically significant at a 1% level; the expected signs of the coefficients of the logit model are correct. On the other hand, the effect of the Juntos Social Program on the length of the working day is negative for the year 2021; it is found that the value of the average treatment effect in the treated population (ATT) is -1.167, which is highly significant at a 1% level. This indicates that participation in the Juntos Social Program is associated with an average reduction of 1.167 hours per week in working hours. This suggests that the economic transfer provided by the program is not sufficient to replace the workday, which implies that beneficiaries must continue to participate in the labor field.